Green Procurement and Service Delivery of County Governments in Western Region, Kenya - Walubengo, Kennedy Wandera (International Journal of Business, Economics, and Social Development, 2024)
The framers of the Public Procurement Law envisaged to streamline how public procurement should be conducted in order to realize value for money in public procuring entities. The primary objective of the research thus was to determine the effect of green procurement on service delivery of County Governments in Western Region, Kenya. The study adopted a positivist research approach and was informed by ecological modernization theory. The study was conducted in Western Region, Kenya in the Counties of Kakamega, Busia, Vihiga, and Bungoma. The study's target population of 228 officials was broken down into chief officers, directors, finance officers, and procurement officers. The study selected 174 participants as its sample. Primary data was gathered through interview schedules and a questionnaire. A pilot study was carried out to test for validity and reliability. The data analysis made use of both descriptive and inferential statistics. SPSS version 26 was used to analyse quantitative data while qualitative data was analysed thematically alongside study objectives. Green procurement was found to be a significant predictor of service delivery in County Governments. Specifically the study's findings showed that Green Procurement explains 23% of variation in service delivery of County Governments in western Kenya Region. Green Procurement had unstandardized regression value of 0.368. This suggested that County Governments in the Western Region, Kenya will boost the delivery of services by 36.8% for each additional unit in green procurement. The study came to the conclusion that there is need for the County Governments to ensure legislation, enforcement and adherence to environmental laws and policies.